2017
DOI: 10.1016/j.cattod.2016.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia decomposition over cobalt/carbon catalysts—Effect of carbon support and electron donating promoter on activity

Abstract: Please cite this article in press as: L. Torrente-Murciano, et al., Ammonia decomposition over cobalt/carbon catalysts-Effect of carbon support and electron donating promoter on activity, Catal. Today (2016), http://dx. a b s t r a c tThis paper sets the new design parameters for the development of low temperature ammonia decomposition catalysts based on readily available cobalt as an alternative to scarce but highly active ruthenium-based catalysts. By using a variety of carbon materials as catalytic supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 36 publications
5
27
0
Order By: Relevance
“…Extensive studies have shed light on the ammonia decomposition mechanisms on various metals, such as Fe, [7][8][9] Ni, [10][11][12][13] Co, 14,15 Cu(111), 16 Pd(111), 17 Pt, 18 Rh(111), 19 Ru(0001) [20][21][22][23][24][25][26][27] and Ir. [28][29][30][31][32] Boisen employed a model describing the catalytic trends over transition metal catalysts and found Ru to be the most active metal for this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shed light on the ammonia decomposition mechanisms on various metals, such as Fe, [7][8][9] Ni, [10][11][12][13] Co, 14,15 Cu(111), 16 Pd(111), 17 Pt, 18 Rh(111), 19 Ru(0001) [20][21][22][23][24][25][26][27] and Ir. [28][29][30][31][32] Boisen employed a model describing the catalytic trends over transition metal catalysts and found Ru to be the most active metal for this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed studies on metal-ammonia interaction have been published using theoretical ways, in which the effect of support is not considered. Results suggest that the adsorption of ammonia on transition metal atoms, like Fe and Ni, occurs in bridge, hollow, and top positions, through the unpaired electrons in nitrogen [56][57][58]. Their results suggest a chemical interaction between ammonia and metals supported by calculated thermodynamics parameters.…”
Section: Conditionsmentioning
confidence: 90%
“…Yin et al (2004b) found that a multiwall carbon nanotube-supported Ru catalyst exhibited the best performance for catalytic NH 3 decomposition among the catalysts they tested. Moreover, the catalytic performance of supported metal catalysts has been improved by adding promoters (Raróg-Pilecka et al, 2003;Sørensen et al, 2006;Huang et al, 2013;Mukherjee et al, 2018;Su et al, 2018;Hu et al, 2019;McCullough et al, 2020) and by modifying the support (Yin et al, 2004a;García-García et al, 2010;Armenise et al, 2012;Marco et al, 2013;Bell et al, 2017;Ren et al, 2017;Mukherjee et al, 2018;Su et al, 2018;Sima et al, 2020). Although most studies focus on Ru or Ni metal as the active site for NH 3 decomposition to produce H 2 (Choudhary et al, 2001;Raróg-Pilecka et al, 2003;Yin et al, 2004aYin et al, , 2004bSørensen et al, 2006;García-García et al, 2010;Armenise et al, 2012;Huang et al, 2013;Marco et al, 2013;Nakamura and Fujitani, 2016;Okura et al, 2016;Takahashi and Fujitani, 2016;Bell et al, 2017;Ren et al, 2017;Mukherjee et al, 2018;Su et al, 2018;Hu et al, 2019;Lucentini et al, 2019;McCullough et al, 2020;Sima et al, 2020), supported nonnoble metal catalysts and transition metal…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies focus on Ru or Ni metal as the active site for NH 3 decomposition to produce H 2 (Choudhary et al, 2001;Raróg-Pilecka et al, 2003;Yin et al, 2004aYin et al, , 2004bSørensen et al, 2006;García-García et al, 2010;Armenise et al, 2012;Huang et al, 2013;Marco et al, 2013;Nakamura and Fujitani, 2016;Okura et al, 2016;Takahashi and Fujitani, 2016;Bell et al, 2017;Ren et al, 2017;Mukherjee et al, 2018;Su et al, 2018;Hu et al, 2019;Lucentini et al, 2019;McCullough et al, 2020;Sima et al, 2020), supported nonnoble metal catalysts and transition metal (Co, Fe, Mo, and Ni) nitride or carbide catalysts have been reported as active catalysts for producing H 2 via NH 3 decomposition (Podila et al, 2017;Srifa et al, 2017;Torrente-Murciano et al, 2017;Jolaoso et al, 2018;Lara-García et al, 2019). Although these catalysts are relatively inexpensive, they exhibit high performance for NH 3 decomposition only at temperatures above 823 K (Bell and Torrente-Murciano, 2016;Podila et al, 2017;Srifa et al, 2017;Torrente-Murciano et al, 2017;Jolaoso et al, 2018;Lara-García et al, 2019). ese inexpensive catalysts would be suitable for high-temperature applications, such as in solid oxide fuel cells with NH 3 as a fuel, but not for on-site H 2 production at low temperatures (Bell and Torrente-Murciano, 2016).…”
Section: Introductionmentioning
confidence: 99%